EFFECTS OF MEDICINAL BIOMAGNETISM AND DEMAG ON SEVERE DEPRESSION: A MIXED STUDY CONDUCTED IN A CAPS II - Santana de Assis, Claudia; Viapiana Bossa, Adriane (Health and Society, 2025)
Depression is a prevalent mental disorder invariably accompanied by emotional and physical impairments, as well as limitations in conventional treatment. This study investigated the effects of Magnetic Integrative and Complementary Practices (PICMAG), specifically Medical Biomagnetism (BM) and Magnetic Emotional Dispersion (DEMAG), in managing severe and persistent depression in patients treated at a Psychosocial Care Center (CAPS) within the Brazilian Unified Health System (SUS). The research adopted a mixed-methods approach, combining quantitative and qualitative analyses, involving three participants who underwent eight therapeutic sessions over four weeks. The impact of the interventions was assessed through the WHOQOL-BREF questionnaire and semi-structured interviews. The results indicated a significant improvement in the physical, psychological, and social domains, with a reduction in depressive symptoms, increased vitality, improved sleep quality, and strengthened social interactions, along with notable gains in self-esteem and mood. Qualitative reports reinforced these findings, highlighting emotional relief and the reframing of negative behavioral patterns. Additionally, biomagnetic pairs and destructive mental, behavioral, and attitudinal states (ECADs) were identified suggesting a link between bioenergetic imbalances and depressive symptoms. The analysis suggests that BM and DEMAG may modulate neurochemical and inflammatory activity, promoting emotional stability and symptom relief. Despite limitations such as the small sample size and the absence of a control group, the results point to the potential of these techniques as complementary approaches in mental health care. Future studies with larger samples and neurochemical biomarker monitoring may contribute to validating the efficacy of PICMAG and supporting its incorporation into the Psychosocial Care Network (RAPS) of SUS.